ANALISA KUALITAS PELAYANAN JASA TERHADAP KEPUASAN PELANGGAN PADA PDAM TIRTA MUSI UNIT KALIDONI PALEMBANG (Studi Kasus) - H.L. Suhairi Hazisma; Yusnizal Firdaus; Alhushori . (Universitas PGRI Palembang, 2013)
The Aim of this research is to know the influence of the quality of service on the customer satisfaction at PDAM Tirta Musi Unit Kalidoni Palembang. Population of this research are all customer of PDAM Tirta Musi Unit Kalidoni Palembang in May 2012. Sample of this research are 100 respondents, the author use simple random sampling technique for this research. Data analysis used the method of interviews and questionnaires. This research is using a simple regression analysis using two variables: Service quality variables as dependent variables and customer satisfaction as independent variables. Based on calculation using the program SPSS 17.0 version showed that the value of R Square affect customer satisfaction of 33,7%, which means 33,7% of customer satisfaction is influenced by the quality of service and the remaining 66,3% influenced by other factors. Based on the results of this final report, the author suggest that PDAM Tirta Musi Unit Kalidoni Palembang should further enhance the service quality of its services in order to give more satisfaction to customers. Keywords: Costumers, Satisfaction, Services, Quality